Pola Interaksi Edukatif Guru dan Siswa dalam Proses Pembelajaran Bahasa Arab di SMK Islamic Centre Baiturrahman - Nasywa Aulia (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to examine the patterns of educative interaction between teachers and students in the process of Arabic language learning within the context of Islamic education, specifically at SMK Islamic Centre Baiturrahman. The research adopts a qualitative approach using a library research method, in which data were collected from various academic sources such as books, journals, scholarly articles, and relevant educational documents. The data were analyzed descriptively and analytically to identify forms of interaction, the teacher’s role, and the challenges encountered in the learning process. The findings reveal that effective educative interaction is characterized by two-way or multi-directional communication involving active student participation, constructive feedback from teachers, and a supportive classroom atmosphere. However, Arabic language instruction faces several challenges, including students’ limited vocabulary, lack of confidence in speaking, monotonous teaching methods, and insufficient Arabic-speaking environments. Teachers play a crucial role in shaping positive interactions through communicative, empathetic, and adaptive teaching approaches. This study emphasizes the importance of designing Arabic learning strategies that are more interactive, student-centered, and contextually relevant. It also underlines the need to integrate pedagogical practices with Islamic values to foster a holistic learning environment. The outcomes of this research are expected to contribute to the development of more effective Arabic language teaching models in Islamic educational institutions.